Menggagas Inovasi Madrasah Ibtidaiyah di Era Digital Perspektif Kebutuhan dan Harapan Pelanggan - Nijo Nijo; Wahab Wahab (Syntax Corporation Indonesia, 2024)
This research aims to initiate innovations that can build and maintain the existence of Madrasah Ibtidaiyah (MI) in the digital era, taking into account the perspective of customer needs and expectations. The digital era brings challenges as well as opportunities for Islamic educational institutions, including MI, to adopt technology in the learning process and education management. This study examines how MI can adapt to the development of digital technology without ignoring Islamic values that are the foundation of education. Through the literature research method, this study analyzes various literature related to technology adaptation in education, and explores strategies that have been successfully implemented in other Islamic educational institutions. The results of the study show that the adoption of digital technology in MI can improve teaching effectiveness and strengthen the interaction between teachers and students. However, this adaptation must be done carefully to ensure that technology does not diminish the essence of Islamic teachings. In addition, the study found that MIs that are responsive to customer needs and expectations, such as students, parents, and the community, have higher competitiveness. Collaboration between MI, the government, and the private sector was also identified as an important factor in supporting innovation in MI.